(untitled) (مجلة إحالات, 2026)
Abstract: The epistle repertoire of Ali ibntalib hinges, in the road of eloquence, upon the linguistic argumentation regarded as a linguistic phenomenon available in any speech and document as Ducrot believes; such manifests the argumentative linguistic devices in the repertoire texts; there is a heed to conjunctions, its selection and their position in utterances so as to turn the prow of the speech to then proper destination the addresser desires ant the very out set. Such is known as argumentative conjunction that are of essentiality to make the speech acts consistent , elucidate the conveying process to the addressee and offer the information. Yet imam Ali takes hold of it influence and convey the argumentative intents he means. so we concluded that these linguistic devices to transpire the content to delimit its argumentative function in the language and such grants the speech initiative and influential inauguration and gain the argumentative scope through stimulating the addressee and guiding him to the intent he desires.